Management of Tracheal Diseases in Children - Muthialu, Nagarajan; Ramaswamy, Madhavan; Beeman, Arun; Yeh, Yi-Ting (Frontiers in Pediatrics, 2020)
Tracheal pathology in children are primarily congenital. They can be considered primary or de novo, when this is seen as an inherent defect within the cartilages of the tracheal segment. While segmental cartilage defects are very rare, there are often occasions when one or more cartilages can be considered missing from the length of trachea, contributing to airway abnormality. Secondary tracheal pathologies can often be seen in relation to disorders affecting nearby vascular elements or thoracic cage in general.